Identify of Vietnamese Traditional Culture Through Contemporary Literature - Hue Hoang Thi (Jurusan Sastra Indonesia, 2017)
This article offers a consideration that: the cultural characteristics of each nation, in the era of information technology, are created and stored through a system of cultural values, symbols, in literature. Culture and literature dominant, interactions mutual influence. So itinerary search, decode literary from the cultural perspective is the journey back to my roots and culture conviction the value of truth, goodness, beauty of the nation. Vietnamese literature achievements proves literature is a form of cultural memory handed down, at the same time, demonstrates the similarities message, the premonition of the artist with the past and future of the nation and humanity. Tran Thuy Mai’s stories are full of Hue culture, Hue soul, from nature to daily life, customs to characters of Hue people. It is the special and distinguishable value of Tran Thuy Mai’s short stories in Vietnam contemporary literature.